(untitled) (Revista de História Regional, 2007)
This paper aims to show the transformation variety presence in ecumenical movement beginning which occurred in Protestantism and produced an original religious approach. This approach contains self characteristics that led to the protestants unity search and transformed several life aspects of modern society.